Penguatan Modal Sosial Melalui Nilai Mapalus pada Pembelajaran Pendidikan IPS - Sulistyosari, Yunike; Ida Bagus Weda Wigena; Ida Kristianti Waruwu (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
Social capital is a key aspect in nurturing inclusive and sustainable learners. Efforts to strengthen social capital in students in this era of globalization can be achieved through the integration of the "mapalus" values into Social Studies (IPS) education. This research employs a qualitative approach with data collection methods including interviews with teachers and students, observations, and document analysis. The findings of this study indicate that the integration of "mapalus" values into IPS education can be considered an effective strategy for enhancing students' social capital. Mapalus-based IPS learning encourages students to become active and responsible members of society. The local wisdom of "mapalus" values applied teaches the importance of mutual assistance and the development of social skills in students.